1998
DOI: 10.1161/01.atv.18.12.1942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Novel Antiplatelet Agent Cilostazol on Plasma Lipoproteins in Patients With Intermittent Claudication

Abstract: Abstract-Cilostazol is an antiplatelet agent and vasodilator marketed in Japan for treatment of ischemic symptoms of peripheral vascular disease. It is currently being evaluated in the United States for treatment of symptomatic intermittent claudication (IC). Cilostazol has been shown to improve walking distance in patients with IC. In addition to its reported vasodilator and antiplatelet effects, cilostazol has been proposed to have beneficial effects on plasma lipoproteins. We examined the effect of cilostaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
132
2
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(150 citation statements)
references
References 18 publications
(10 reference statements)
11
132
2
5
Order By: Relevance
“…This drug promotes lower TG levels, increases HDL in patients with POAD 41 , improves postprandial lipemia in patients with DM 42 , increases NO expression, has a positive effect on apoptosis, prevents thrombosis after stenting and has demonstrated the ability to interfere in various stages of the atherosclerotic process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug promotes lower TG levels, increases HDL in patients with POAD 41 , improves postprandial lipemia in patients with DM 42 , increases NO expression, has a positive effect on apoptosis, prevents thrombosis after stenting and has demonstrated the ability to interfere in various stages of the atherosclerotic process.…”
Section: Resultsmentioning
confidence: 99%
“…In 189 individuals with POAD and without hyperlipidemia, cilostazol reduced TG by 15% and increased HDL by 9.5%, in a double blind multicenter study, controlled with placebo and twelve weeks of follow-up 41 . It also improved postprandial lipemia in 112 patients with type 2 DM or glucose intolerance, controlled with placebo during twelve weeks of follow-up 42 .…”
Section: The Effect Of Cilostazol On Dyslipidemiamentioning
confidence: 99%
“…Cilostazol has been shown to significantly increase (35-109%) walking distance in people with claudication in several large double blind placebo controlled randomized trials (Money et al, 1998, Elam et al, 1998). The precise role of cilostazol remains to be defined, but a trial of the drug is probably indicated in patients who have unacceptable symptoms despite three to six months of adherence to best medical treatment.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…In studies in which the ABI was evaluated, improvement was also noted in this parameter compared with placebo. 25,27 The beneficial effects of cilostazol on serum lipids have also been demonstrated in patients with IC. After 12 weeks of cilostazol therapy (100 mg b.i.d.)…”
Section: Effect Of Cilostazol On Clinical Trial Endpointsmentioning
confidence: 99%
“…Cilostazol treatment in these patients resulted in statistically significant increases in treadmill walking time (35%) and in the ABI (9%), thus indicating that the drug simultaneously improves physical capacity and plasma lipid profiles. 27 In studies that have looked at HQL measures in patients with IC, 11,25 the physical health concepts of the SF-36 showed improvement at 16-24 weeks in patients on cilostazol. Similarly, there were improvements in patients' perceptions of walking speed and distance on the WIQ, as well as walking pain/discomfort on the COM.…”
Section: Effect Of Cilostazol On Clinical Trial Endpointsmentioning
confidence: 99%